1991
DOI: 10.1063/1.460082
|View full text |Cite
|
Sign up to set email alerts
|

Surface structure and thermal motion of n-alkane thiols self-assembled on Au(111) studied by low energy helium diffraction

Abstract: Low energy helium diffraction has been used to study the packing and thermal motion of the terminal CH3 groups of monolayers of n-alkane thiols self-assembled on Au(111)/mica films and a Au(111) single crystal surface. At low temperatures (<100 K), the terminal CH3 groups are arranged in domains containing a hexagonal lattice with a lattice constant of 5.01 Å. As the length of the carbon chain is shortened, an abrupt decrease in the diffraction peak intensities is observed for CH3(CH2)9SH/Au(111)/mica, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
161
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(179 citation statements)
references
References 39 publications
16
161
0
2
Order By: Relevance
“…47 Well depths for a variety of alkanethiol self-assembled monolayers that possess terminal methyl groups have been calculated and the results range from 6.8 to 8.1 meV depending on odd/even effects of the alkane chain length. 7,55 The average well depth of 6.75 meV for He-CH 3 -Si͑111͒ is thus in excellent agreement with that reported for other, similar systems.…”
Section: ͑9͒supporting
confidence: 78%
See 3 more Smart Citations
“…47 Well depths for a variety of alkanethiol self-assembled monolayers that possess terminal methyl groups have been calculated and the results range from 6.8 to 8.1 meV depending on odd/even effects of the alkane chain length. 7,55 The average well depth of 6.75 meV for He-CH 3 -Si͑111͒ is thus in excellent agreement with that reported for other, similar systems.…”
Section: ͑9͒supporting
confidence: 78%
“…The well depths determined from the intercepts were D H = 7.5Ϯ 2.6 meV and D D = 6.0Ϯ 3.9 meV, which are in agreement with other methyl-terminated systems. 7,47 We note that the well depths are equal within the precision of the measurement, as expected, since isotopic substitution does not alter the Hesurface attractive potential. In subsequent sections, unless otherwise stated we will use the experimentally determined values of the well depth, noting that the use of the average value of 6.75 meV changes the results of our calculations by less than 5%.…”
Section: ͑9͒mentioning
confidence: 56%
See 2 more Smart Citations
“…Early experimental He diffraction studies established a ( √ 3 × √ 3)R30 • structure for alkylthiolates on Au(111) with one molecule per surface unit cell resulting in a 1/3 monolayer coverage [106,107]. Later He diffraction and grazing incidence x-ray diffraction (GXRD) studies found a 3 × 2 √ 3 superstructure † .…”
Section: Sam Induced Surface Reconstructionsmentioning
confidence: 99%